Vocational education and training in Malta : short description - (:unkn) unknown (Publications Office of the European Union, 2017)
"Unlike many other EU Member States, unemployment in Malta is not a major labour market problem. Its dynamic economy developed fast and withstood the crisis well. New sectors are emerging and employment has been growing. In a context of low educational attainment, high early leaving and an ageing population, this has led to skill shortages in several key sectors of the economy. This first short description on VET in Malta aims to contribute to better understanding of the system and recent developments. It analyses trends, contextualises policy responses and highlights areas of recent progress. The report paints a picture of an expanding and dynamically renewing VET system shaped by reforms that have been at the heart of Malta's response to social and economic challenges." (Editor, BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; G 1.2.3 Qualifikationsentwicklungen; Berufsbildungssystem; Berufsbildungspolitik; Qualifikationsentwicklung; Qualifikationsbedarf; Bildungsreform; Malta